(untitled) (Revista LIDER, 2021)
The purpose of this article is to analyze the social fragmentation and the inequalities in the Metropolitan Area of Montevideo, according to our recent study and publication (Veiga and Rivoir 2007). In this regard, we analyze first, the profiles and trends of the various sub metropolitan, based on the analysis of quantitative indicators and Household Surveys, illustrating their socio-economic characteristics, and processes of spatial segregation and inequality that are taking place there, with special attention to the phenomena of social and economic fragmentation. We analyze the issues of territorial inequalities and socio-economic segregation; differentiations and social exclusion and social stratification and polarization. Secondly, we illustrate the characteristics of local societies in sub metropolitan areas from the vision of local actors. The information presented in this case, is based upon interviews with qualified informants in the various zones, which by its institutional relation, or his knowledge, can provide information and opinion to the sociological study of the area. On this regard, we analyze the perception of problems and social inequalities and cultural changes, lifestyles and the problems of local identity. Thirdly, there is a synthesis and conclusions.